(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This research examines how words are utilised to communicate meaning in selected X posts on the 2024 Gen Z slang No Gree for Anybody. “X” is a social media platform formerly known as Twitter. It is an internet platform that encourages interaction on topical socio-political, religious, economic and other sundry issues. Previous research in this field has focused on the study of words and their usage in different contexts. In continuation with the existing scholarship, this research explores the Gen Z usage of the slang, No Gree for Anybody, and the various meanings generated from its usage on the X space. Thus, this work identifies different contexts where the slang is employed, its function in such contexts, and its impact on the X space. The paper adopts M. A. K Halliday’s systemic functional grammar, particularly for its concern on the usage and functions of language in context. The study employs a qualitative approach, utilising selected media posts relevant to the slang No Gree for Anybody on the X space. The data for the analysis were collected from tweets, retweets, posts, comments and replies made by social actors on the selected social media platform. This paper discovers that the Gen Z deploy a distinct style in their lexical choices to express different views through the use of the slang. More so, the study finds that the slang No Gree for Anybody as used by social actors can connote a sense of motivation for self-improvement or a resistance against an oppressive system. The study concludes that the media space, specifically the X platform serves as a powerful platform for self-expression and the creation of meaningful change.